Dynamic Modeling and Combination Analysis of Plunger Valve Considering Both Flow and Actuator - Y. Ren; C. Bai; H. Zhang (Journal of Applied Fluid Mechanics, 2023)
The plunger valve has an important role in a large compressor system as its operating characteristics directly affect the aerodynamic boundary condition of the compressor equipment. In this study, dynamic modeling and analysis method of the plunger valve are proposed for an accurate control of the system. By considering the interaction between the dynamic flow in the valve and actuator action, a lumped parameter model for the fluid–structure interaction force and multibody dynamic model of the actuator are developed based on intrinsic correlation parameters. A combination analysis to simultaneously predict valve flow and actuator dynamic characteristics is proposed. The predicted results are in a good agreement with experimental data, which validates the proposed model and analysis method. The analysis results show that the coupling effect between the valve flow and actuator is significant and has an important role in valve control, particularly when the valve opening is smaller. Compared to the experimental data and computational fluid dynamics results, the presented methods are accurate for valve control and effective for prediction of flow rate.